A 3D porphyrinic metal-organic framework with fsc topology for efficient visible-light-driven photocatalytic degradation. (1st November 2022) - Jiang, Wei; Li, Jinlai; Jiang, Yu; Zhou, Shi; Liu, Bo; Zhou, Tianyu; Liu, Chunbo; Che, Guangbo
Graphical abstract: A porphyrinic metal–organic framework with the fsc topology has been constructed, demonstrating efficient and durable photocatalytic performance for degradation of methylene blue. Abstract: The design and construction of efficient photocatalysts are of great significance for environmental remediation. Herein, a novel porphyrinic MOF, [Cd3 (tipp)(fum)2 (DMSO)]n ·3nDMF·0.5nIPA (JLNU-101 ), was synthesized by using 5, 10, 15, 20-tetrakis(4-(imidazol-1-yl)phenyl)porphyrin (H2 tipp) and fumaric acid (H2 fum) as linkers. In JLNU-101, [Cd2 ] clusters are coordinated by Cd-tipp and fum 2- ligands to give a 3D framework, which could be simplified as having an uncommon fsc topology. Owing to the suitable energy band structure, JLNU-101 showed efficient and durable photocatalytic performance for the degradation of methylene blue (MB). Ecotoxicological assessment verified the decreased toxicity of the decomposed intermediates. Structure characterization demonstrated that the chemical bonds, optical property, morphology and composition were maintained well during the photocatalysis. This work provides an insight to design functional MOFs for photocatalytic degradation.